Sistem Monitoring Local Area Network Pelanggan PT. PHE ONWJ Pada PT. Patrakom Jakarta - Yayan Hendrian; Dalhar Dalhar (JURNAL TEKNIK KOMPUTER, 2021)
PT. Patrakom as a company engaged in telecommunications, has many customers in the remote areas across Indonesia. Use satellite transmission media, data can be sent and from various cities in Indonesia. There are many customers in a location that is quite difficult to reach. One that is difficult to reach customers and need special monitoring system, namely Drilling PT. PHE ONWJ (Pertamina Hulu Energi Offshore North West Java) which is located in the Java Sea. Customer's computer network monitoring system PT. PHE ONWJ At PT.Patrakom currently still using PRTG Network Monitoring (network monitoring application) which only Displays graphs of bandwidth usage by user. Thus resulting in a notice to the engineer during a network interruption or VSAT link down time can not be disclosed in a fast time. Engineer and the NCC (Network Central Controler) must check the PRTG to detect network intrusions. The absence of notice to the engineer automatically lead to treatment interruption takes longer. Use network monitoring system based on SMS (Short Message Service) enables the earliest possible notification to the engineer when the network has a problem, so the engineer will be able to directly perform interference checking and will be quickly resolved. With the monitoring sisitem like this will certainly increase customer satisfaction with the services provided by PT.Patrakom